Rationale-based defences in criminal law "I did it. I chose to do it. And here's why..." - Dsouza, Mark (Hart Publishing, 2017)
This book offers a novel, principled, and intuitively appealing conceptual account of the natures of justifications and excuses, showing how they differ, and why the distinction between them matters. This model is shown to generate appealing liability outcomes, advance convincing solutions to questions that have puzzled criminal lawyers for years, and offer suggestions for doctrinal reform that are both normatively sound, and practical. By proposing new ways to think about defences, this book makes an original contribution to criminal law theory that will be of benefit to academics, practitioners, and persons interested in law reform.